2000
DOI: 10.1038/modpathol.3880091
|View full text |Cite
|
Sign up to set email alerts
|

Needle Biopsy of Recurrent Adenocarcinoma of the Prostate After Radical Prostatectomy

Abstract: The objective of this study was to evaluate needle biopsy of recurrent prostate cancer after radical prostatectomy. We evaluated 37 cases of recurrent prostate cancer after radical prostatectomy that were diagnosed by needle biopsy between March 1984 and July 1998. Fifteen were from consultations in which contributors were uncertain of the diagnosis, and 22 were from men who had come to The Johns Hopkins Hospital for treatment. The median interval from radical prostatectomy to biopsy showing recurrent tumor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Interestingly, they report six cases where only benign prostate tissue was recovered from biopsy specimens. Ripple et al 41 have reported on the anastomotic biopsy pathology of a series (no. 37) of locally recurrent cases proved by transrectal ultrasound biopsy, and came with the interesting finding of coexisting benign prostatic acini in 14% of these biopsies.…”
Section: Diagnostic Accuracy: Histological Outcomementioning
confidence: 99%
“…Interestingly, they report six cases where only benign prostate tissue was recovered from biopsy specimens. Ripple et al 41 have reported on the anastomotic biopsy pathology of a series (no. 37) of locally recurrent cases proved by transrectal ultrasound biopsy, and came with the interesting finding of coexisting benign prostatic acini in 14% of these biopsies.…”
Section: Diagnostic Accuracy: Histological Outcomementioning
confidence: 99%